Integrating the Extended Theory of Planned Behavior With the Stages of Change to Predict Exercise Among Chinese People With Type 2 Diabetes - Gao, Min; Chen, Ping; Sun, Xinying; Feng, XingLin; Fisher, Edwin B. (Frontiers in Public Health, 2021)
Background: There have been very limited prospective studies examining social-cognitive models within stages of behavior change in the exercise domain. Purpose: We examined the utility of the theory of planned behavior (TPB), incorporating self-identity and descriptive norm constructs, to predict exercise behavior across the stages of change, in individuals with type 2 diabetes. Methods: Data were obtained from a longitudinal study. Multi-group structural equation modelling was used to estimate the association between extended TPB constructs and exercise within different stage groups. Results: 647 individuals completed a self-report questionnaire at baseline and at 3 months follow-up. The extended TPB model explained 8%-15% variance of exercise behavior and 42%-81% variance of exercise intention within three stage groups in the cross-sectional design. The extended TPB model explained 4%-13% variance of exercise behavior and 42%-66% variance of exercise intention in the longitudinal design. Intention was significantly related to exercise behavior in the pre-action and action stages. Self-identity, perceived behavioral control and descriptive norms were stronger predictors of intention in different stages. Conclusion: Discontinuity patterns in the extended theory of planned behavior for the different stage groups were found. Intention was a significant predictor of exercise in the pre-action and action stages at 3 months.